49x^3-14x^2y+xy^2
x^4+4
4x^4+y^4
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(x+\frac{1}{2}\right)^2-\left(x+\frac{1}{2}\right)\left(x+6\right)=8\)
\(\Leftrightarrow\frac{\left(2x+1\right)^2}{4}-\frac{\left(2x+1\right)\left(x+6\right)}{2}=8\)
\(\Leftrightarrow\left(2x+1\right)^2-2\left(2x+1\right)\left(x+6\right)=32\)
\(\Leftrightarrow-22x-43=0\Leftrightarrow x=\frac{43}{-22}\)
\(a,a^2-6a+9\)
\(=a^2-2.a.3+3^2\)
\(=\left(a-3\right)^2\)
\(b,\frac{1}{4}x^2+2xy^2+4y^4\)
\(=\left(\frac{1}{2}x\right)^2+2.\frac{1}{4}x.4y^2+\left(4y^2\right)^2\)
\(=\left(\frac{1}{2}x+4y^2\right)\)
\(x^4+4=\left(x^4+4x^2+4\right)-4x^2=\left(x^2+2\right)^2-4x^2=\left(x^2-2x+2\right)\left(x^2+2x+2\right)\)
\(4x^4+y^4=\left(4x^4+y^4+4x^2y^2\right)-4x^2y^2\)
\(=\left(2x^2+y^2\right)^2-4x^2y^2=\left(2x^2-2xy+y^2\right)\left(2x^2+2xy+y^2\right)\)